Microbial and Amino Acid Changes in Preand Post- Fermentation Shrimp Paste from Cirebon, West Java - Nadhira P. Dian; Radestya Triwibowo; Rusky I. Pratama; Novalia Rachmawati (Squalen)
This study investigates the changes in microbial communities and amino acid profiles in shrimp paste (terasi) from Cirebon, West Java, before and after fermentation. Samples were collected from two traditional processors, representing different stages of shrimp paste processing. The microbial diversity was analyzed using 16S rRNA gene sequencing, revealing significant shifts in bacterial populations during fermentation. Processor A’s shrimp paste showed a dominance of Bacilli, with Staphylococcus becoming more prevalent post-fermentation, while Processor B’s paste exhibited a more diverse microbial community, including Empedobacter and Acinetobacter. The study identified 60 and 64 genera in Processor A’s samples before and after fermentation, respectively, and 26 and 41 genera in Processor B’s samples. Vibrio, initially present in the raw material, was eliminated post-fermentation. Amino acid analysis indicated an increase in key amino acids such as glutamic acid and leucine post-fermentation, contributing to the enhanced flavor profile of the shrimp paste. Processor A’s shrimp paste showed significant increases in amino acids, with glutamic acid reaching 64,249 mg/kg, Processor B’s paste had a more moderate increase, with glutamic acid at 10,714 mg/kg postfermentation. These findings highlight the significant influence of fermentation conditions on the microbial and biochemical composition of shrimp paste, emphasizing the importance of standardized processing methods to ensure consistent product quality and safety.